Beyond NPM to Post-NPM? A Study of China's Government Reforms Over the Past 40 Years. Issue 7 (October 2019) - Xiaolong, Tian; Christensen, Tom
This article examines China's government reforms over the past 40 years from an instrumental–structural and a cultural–value perspective with the aim of exploring the supposed shift from New Public Management (NPM) to post-NPM. It finds that some aspects of the Old Public Administration (OPA) have been combined with NPM and post-NPM features in a layering process, resulting in new hybrid organizational forms and value orientations. In particular, the analysis shows that China's post-NPM-oriented reforms have focused on positive coordination in the sense of super-ministries and networks on the one hand and value-based governance with a service orientation on the other hand.